Effects of Perceived Workplace Incivility on Presenteeism Perceptions: A Research in Turkey - Kumral, Tuğçe; AYRANCI, EVREN (My University, 2020)
There are many different presenteeism conceptualizations in the business literature, and despite some insights about underlaying presenteeism factors, further research is still needed in this emerging area. One of such factors is claimed to be incivility within the business context. There is, however, not ample research about these factor’s connections with presenteeism itself. Taking this gap into account, the aim of this study is to scrutinize any possible effects of business members’ perceived workplace incivility on their presenteeism perceptions. Data are collected via questionnaires from the members of small and medium sized enterprises (SMEs) in Ikitelli Organized Industrial Zone in Istanbul, Turkey. A total of 183 participants are contacted. There is a statistically significant connection between the participants’ perceived incivility and presenteeism, implying that these two negative business aspects are actually related. This finding clearly points out that perceptions of undesirable, rude, and negative behaviors in the work context is a motivator of the participants’ unwillingness to be present in their business environment. It is also noteworthy that the perceived incivility is a monolithic aspect, whereas the perception of presenteeism is composed of perceptions about negativities and resistance, both of which are related to issues in business context.
Keywords: Perceived presenteeism; Perceived workplace incivility; Small and medium sized enterprises